2003
DOI: 10.1002/jbt.10077
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of herbicide dicamba and related compound on plant mitochondrial bioenergetics

Abstract: The herbicide dicamba (3,6-dichloro-2-methoxybenzoic acid) was evaluated for its effects on bioenergetic activities of potato tuber mitochondria to elucidate putative mechanisms of action and to compare its toxicity with 2-chlorobenzoic acid. Dicamba (4 mol/mg mitochondrial protein) induces a limited stimulation of state 4 respiration of ca. 10%, and the above concentrations significantly inhibit respiration, whereas 2-chlorobenzoic acid maximally stimulates state 4 respiration (ca. 50%) at about 25 mol/mg mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Through all examples cited previously, it is clear that cytotoxicity of air pollutants (PM, PAHs, metals, or herbicides) in various cells [70, 78, 133] mainly incriminates the excessive production of ROS capable of targeting mitochondria by different mechanisms (Figure 1) [83, 134]. At the same time as the ROS-dependent apoptosis, some other oxidative stress-independent signaling pathways have been identified.…”
Section: Air Pollutants and Cytotoxic Cell Deathmentioning
confidence: 99%
“…Through all examples cited previously, it is clear that cytotoxicity of air pollutants (PM, PAHs, metals, or herbicides) in various cells [70, 78, 133] mainly incriminates the excessive production of ROS capable of targeting mitochondria by different mechanisms (Figure 1) [83, 134]. At the same time as the ROS-dependent apoptosis, some other oxidative stress-independent signaling pathways have been identified.…”
Section: Air Pollutants and Cytotoxic Cell Deathmentioning
confidence: 99%
“…From these results it was concluded that dicamba decreases oxidative phosphorylation by a dual effect on the redox chain (inhibition of redox complexes, and stimulation of proton leakage through the mitochondrial inner membrane) (Peixoto et al, 2003a). Similarly to rat liver mitochondria, dicamba interfered with potato tuber mitochondria by inhibiting the activities of the respiratory complexes II and III, of ATP synthase, and also stimulating the proton leakage through the mitochondrial inner membrane (Peixoto et al, 2003b). In turn, comparative effects of dicamba and a related compound, 2-chlorobenzoic acid, on potato tuber mitochondria showed that dicamba is a stronger mitochondrial respiratory chain inhibitor and uncoupler.…”
Section: Dicambamentioning
confidence: 96%
“…In turn, comparative effects of dicamba and a related compound, 2-chlorobenzoic acid, on potato tuber mitochondria showed that dicamba is a stronger mitochondrial respiratory chain inhibitor and uncoupler. So, considering the results, it was suggested that differences in the lipophilicity due to their chemical structures are related to the different sensitivities of mitochondrial bioenergetics to the referred compounds (Peixoto et al, 2003b).…”
Section: Dicambamentioning
confidence: 99%